Bioturbation and erosion rates along the soil‐hillslope conveyor belt, part 1: Insights from single‐grain feldspar luminescence - Román‐Sánchez, Andrea; Reimann, Tony; Wallinga, Jakob; Vanwalleghem, Tom (Earth surface processes and landforms, 2019)
The interplay of bioturbation, soil production and long‐term erosion–deposition in soil and landscape co‐evolution is poorly understood. Single‐grain post‐infrared infrared stimulated luminescence (post‐IR IRSL) measurements on sand‐sized grains of feldspar from the soil matrix can provide direct information on all three processes. To explore the potential of this novel method, we propose a conceptual model of how post‐IR IRSL‐derived burial age and fraction of surface‐visiting grains change with soil depth and along a hillslope catena. We then tested this conceptual model by comparison with post‐IR IRSL results for 15 samples taken at different depths within four soil profiles along a hillslope catena in the Santa Clotilde Critical Zone Observatory (southern Spain). In our work, we observed clear differences in apparent post‐IR IRSL burial age distributions with depth along the catena, with younger ages and more linear age–depth structure for the hill‐base profile, indicating the influence of lateral deposition processes. We noted shallower soils and truncated burial age–depth functions for the two erosional mid‐slope profiles, and an exponential decline of burial age with depth for the hill‐top profile. We suggest that the downslope increase in the fraction of surface‐visiting grains at intermediate depths (20 cm) indicates creep to be the dominant erosion process. Our study demonstrates that single‐grain feldspar luminescence signature‐depth profiles provide a new way of tracing vertical and lateral soil mixing and transport processes. In addition, we propose a new objective luminescence‐based criterion for mapping the soil‐bedrock boundary, thus producing soil depths in better agreement with geomorphological process considerations. Our work highlights the possibilities of feldspar single grain techniques to provide quantitative insights into soil production, bioturbation and erosion–deposition. © 2019 The Authors. Earth Surface Processes and Landforms Published by John Wiley & Sons Ltd. We successfully reconstruct soil reworking using feldspar single‐grain luminescence. A new conceptual model explains the observed luminescence trends along a hillslope catena. We are able to disentangle bioturbation, soil production and erosion/ deposition based on two luminescence proxies. Luminescence data provides more robust measures of soil thickness than field observations.